Designing a Real-Time TKDN Monitoring Dashboard Concept as a Decision Support System Aligned with Akhlak Values at PT Bukit Asam - Sarendra, Tania Citra; Putro, Utomo Sarjono (Universitas KH. Abdul Chalim Mojokerto, 2025)
The Domestic Component Level (Tingkat Komponen Dalam Negeri/TKDN) policy is a key instrument of the Indonesian government to strengthen national industries through procurement activities. For state-owned enterprises (SOEs) such as PT Bukit Asam Tbk (PTBA), TKDN implementation must also reflect AKHLAK values as ethical guidelines for governance. Although PTBA has consistently met TKDN targets, reporting remains manual, relying on Excel and a single person-in-charge. This condition creates inefficiencies, risks of data inconsistency, and limited responsiveness to urgent requests from regulators. This study addresses the problem of the absence of an integrated mechanism to monitor TKDN realization in real time within PTBA’s electronic procurement system (SPEND). The research objective is to design a TKDN monitoring dashboard conceptualized as a Decision Support System (DSS) that incorporates automation, user-centered design (UCD), and AKHLAK values. An exploratory qualitative method was employed, combining semi-structured interviews, participant observation, and document review. Data were analyzed using thematic coding, supported by SWOT analysis, to identify system gaps, user requirements, and ethical value integration. UCD principles were applied to ensure that dashboard features were aligned with stakeholder needs and validated through feedback from key informants. The findings confirm three main themes: limitations of the current reporting system, the need for an interactive dashboard, and the importance of embedding AKHLAK values in system design. A static mock-up was developed, featuring real-time visualization, dynamic filters, role-based access, and modules for certificate management and reporting. This study contributes theoretically by integrating DSS, UCD, knowledge management, and organizational values into dashboard design, and practically by providing PTBA with a blueprint for optimizing SPEND to support more efficient, transparent, and accountable procurement governance.